A comparative experimental investigation on radiant floor heating system and stratum ventilation. (January 2020) - Li, Han; Xi, Chang; Kong, Xiangfei; Lin, Zhang; Wang, Lu
Highlights: A comparison between stratum ventilation and radiant floor heating was studied. Indoor air quality, thermal performance and thermal comfort were discussed. Stratum ventilation can reduce particulate matter related mortality obviously. Stratum ventilation can enhance the indoor comfort by 76.02%. This paper can use as a reference for stratum ventilation on space heating. Abstract: To explore one reasonable ventilation system that can provide a comfortable and healthy indoor environment becomes urgent with the deterioration of outdoor environment. Objective and subjective tests were both employed to investigate the difference in indoor air quality, air pollutant control, thermal performance and thermal comfort. In the objective experiment, research results indicate that the lung cancer mortality caused by the high concentration of PM2.5 and PM10 can be decreased by 28.25% and 58.75% respectively by introducing stratum ventilation in the heavily polluted region. The PM2.5 and PM10 decay duration under radiation floor heating are almost 8–29 times and 4–9 times more than that under stratum ventilation, respectively. Temperature response time under stratum ventilation can be shortened by 30 min compared with that under radiant floor heating. And the average operative temperature difference in the occupied zone is 1.3 °C between stratum ventilation and radiation floor heating. In the subjective experiment, the indoor thermal comfort can be enhanced by 76.02% based on local and overall comfort sensation (LTS and OTS ) by employing stratum ventilation. Replacing the radiant floor heating with stratum ventilation is of obvious significance in the heavily polluted region.